Health related quality of social life - (:unkn) unknown (Gulhane Askeri Tip Akademisi, 2002)
Quality of life is a term which has been used extensively not only by health professional but also philosophers, psychologists, theologists, poets and politicians. Health is a multidimensional phenomenon including not only medical or clinical aspects but also other important dimensions related to the physical, psychological and social aspects of well-being. The richness of the concept requires that for its evaluation multiple dimensions of quality of life are utilized. The concept of quality adjusted life years (QALYs) has become a popular topic among doctors and economists during the last two decades. It combines "quantity i.e., life expectancy with "quality" adjusted life years. The construction of health indices are of fundamental importance for establishing priorities in the health sector and for assesing the objectives of efficiency and effectiveness.
Keywords: Health; Health measurement; QALYs; Quality of life; Social quality of life